Feasibility of Evaluation of Salt Content in Canned Sardine in Oil by Near Infrared Spectroscopy - Sarocha Srikornkarn; Panmanas Sirisomboon (My University, 2014)
This research applied the Near Infrared Spectroscopy (NIRS) in determination of salt content in canned sardines in oil compared with the traditional method which used auto-titrator. The samples were 25 cans (105 g/can) of salt adjusted by adding sodium chloride at different levels (2, 4, 6, 8 and 10 g/can) and another 5 cans were not salt adjusted. Scanning was done by FT-NIR spectrometer (12,500-4,000 cm-1). The model developed by partial least squares regression provided coefficient of determination, root mean square error of cross validation and bias of 89.99%, 0.143% and -0.003%, respectively. This indicated high possibility in applying NIRS.
Keywords: Spectroscopy and Chemometric Analyses